Covalent anchoring of atomically precise glutathione-protected gold nanoclusters on graphene oxide nanosheets. (12th October 2020) - Bertorelle, Franck; Basu, Srestha; Fakhouri, Hussein; Perić Bakulić, Martina; Mignon, Pierre; Russier-Antoine, Isabelle; Brevet, Pierre-François; Thomas, Sabu; Kalarikkal, Nandakumar; Antoine, Rodolphe
Abstract: This paper describes the development of a novel method of producing nanocomposites consisting of gold nanoclusters anchored on graphene oxide nanosheets in a cost-effective and reproducible manner. The novelty of the technique hinges on the covalent functionalization of atomically precise subnanometer gold clusters protected by glutathione (Au15 SG13 and Au25 SG18 ) on to graphene oxide (GO) nanosheets according to the 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride crosslinking method, using the existing carboxylic groups present both at the surfaces of the nanoclusters and the GO nanosheets. The atomic precision of glutathione-protected gold nanoclusters was evidenced by electrospray ionization mass spectrometry. The formed hybrid nanocomposites were characterized by TEM measurements and exhibit nonlinear optical properties characteristic of GO, in particular a strong second harmonic scattering response as well as a multi-photon excited fluorescence spectrum characterized by a broad band in the visible range between 350 and 700 nm. Atomically precise nanoclusters covalently linked to GO nanosheets are therefore promising for new applications in the areas of optoelectronics and photovoltaics.